Model Penilaian Risiko Berbasis Kinerja untuk Rantai Pasok Kelapa Sawit Berkelanjutan di Indonesia - Rika Ampuh Hadiguna (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
As the country's largest palm oil producer in the world, Indonesian palm oil production is still encounter political barriers or non-tariff economy of several countries. Sustainable development policies have a role to overcome these obstacles. The research problem is how to build policies through the performance based risk assessment for sustainable palm oil supply chain in Indonesia. The research objective is to recommend policies that supported by performance-based risk assessment models for sustainable palm oil supply chain in Indonesia. Performance-based risk assessment algorithms have been developed and verified in a comprehensive manner. Model verification is conducted by analyzing the performance of crude palm oil supply chain based on expert’s analysis. This study has obtained the necessary indicators to assess the risk based on performance of sustainable crude palm oil supply chain. Model application has shown that risk level of sustainable crude palm oil in Indonesia relating to economics, environmental, and social aspects are moderate, respectively. However, there are some indicators that need to be considered with the level of risk is quite high, namely demand rate, quality of palm oil, timelines of product delivery, availability of crude palm oil and bullwhip effect. This paper has recommended some policies to address those risks.